(untitled) (Quinto Sol, 2013)
This paper studies the role of political organizations, the church, the state and labor unions in the leisure time of the workers in Northern Patagonia from the beginning of the 19th century, up to the rise of peronismo. We discuss the strategies put into practice by such institutions, as related with the planning and consumption of their spare time. We also analyze each institution´s interests, which went far beyond making themselves sure that the workers´ could take better advantage of their leisure time. Far from that, these actors´ actions were part of a wider strategy that could be combined with the unions´ organizations, such actions were related with the spreading of ideas that could be useful to reinforce consciousness for class struggle, to build a new society and aditionally, to strengthen trade unión structures. The actions of the church, on the other hand, were oriented towards disciplining the working world, christianizing it, and indoctrinating catholic workers in a world of armonic relations between capital and labor and teaching them to reject alterations of the status quo and workers´ ways of participation typical of resistance societies. Finally, actions performed by the State attempted to control,regulate and discipline such workers.